2013
DOI: 10.1007/s00586-013-3019-7
|View full text |Cite
|
Sign up to set email alerts
|

Complications in minimally invasive percutaneous fixation of thoracic and lumbar spine fractures and tumors

Abstract: Purpose We propose to evaluate the complication rate in minimally invasive stabilization (MIS) for spine fractures and tumors, as a common alternative to open fusion and conservative treatment. Methods From 2000 to 2010, 187 patients were treated by minimally invasive percutaneous fixation in 133 traumatic fractures and 54 primitive and/or secondary spine tumors. Complications were classified, according to the period of onset as intraoperative and postoperative, and according to the severity, as major and mino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…Compared to the few available studies (Table 3), our results are consistent [11][12][13][14][15][16][17][18][19]. The largest study by Gasbarrani et al, conducted over a 10 year period from 2000-2010 in a mixed cohort of trauma and metastatic disease patients, reported 15 complications out of the 187 patients included in the report [19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Compared to the few available studies (Table 3), our results are consistent [11][12][13][14][15][16][17][18][19]. The largest study by Gasbarrani et al, conducted over a 10 year period from 2000-2010 in a mixed cohort of trauma and metastatic disease patients, reported 15 complications out of the 187 patients included in the report [19].…”
Section: Discussionsupporting
confidence: 92%
“…Thoracic vertebrae are also at a slightly elevated risk of blood loss than the lumbar vertebrae due to the increased abundance of neurovascular bundles within close proximity [8]. Therefore, easier visualisation and fixation is possible in the lumbar region, accounting for the lower operation time and blood loss reported by Gasbarrani et al [19] In the only animal study, conducted by Lehmann et al, favourable outcomes were demonstrated using percutaneous pedicle screw fixation [17]. The authors performed bilateral pedicle screw fixations on 12 mature sheep at the L4-L6 level.…”
Section: Discussionmentioning
confidence: 95%
“…Complications after PPSI have also been a topic of study within the literature, with a reported incidence in up to 12% of cases (15,17,18,(20)(21)(22)(23) (15). In this cohort, medical and neurologic complications included 1 case of cauda equina syndrome requiring urgent surgical revision, 1 case of wound infection with dehiscence that required surgical debridement with implant removal, and 1 case of nonunion which required anterior thoracoscopic fusion.…”
Section: Percutaneous Pedicle Screw Fixationmentioning
confidence: 92%
“…Percutaneous pedicle screw fixation (PPSI) has been utilized to provide immediate stabilization and adequate reduction in cases of thoracolumbar trauma (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). PPSI without anterior reconstruction or augmentation is primarily utilized in AO type A1 (wedge-compression) and A2 (split) fractures without posterior vertebral wall involvement or significant vertebral body comminution (25).…”
Section: Percutaneous Pedicle Screw Fixationmentioning
confidence: 99%
See 1 more Smart Citation